Clinical implications of convergent procoagulant toxicity and differential antivenom efficacy in Australian elapid snake venoms. (November 2019) - Zdenek, Christina N.; den Brouw, Bianca op; Dashevsky, Daniel; Gloria, Alexandra; Youngman, Nicholas J.; Watson, Ebony; Green, Patrick; Hay, Chris; Dunstan, Nathan; Allen, Luke; Fry, Bryan G.
Highlights: More Australian elapid snakes than recognised previously are potently procoagulant. These species may produce significant clinical effects. Variations in molecular surface results in differential antivenom efficacy. Abstract: Australian elapid snakes are some of the most venomous snakes in the world and are unique among venomous snakes in having mutated forms of the blood clotting factor X in an activated form (FXa) as a key venom component. In human bite victims, an overdose of this activated clotting enzyme results in the systemic consumption of fibrinogen due to the large amounts of endogenous thrombin generated by the conversion of prothrombin to thrombin by venom FXa. Within Australian elapids, such procoagulant venom is currently known from the tiger snake clade ( Hoplocephalus, Notechis, Paroplocephalus, and Tropidechis species), brown/taipan ( Oxyuranus and Pseudonaja species) clade, and the red-bellied black snake Pseudechis porphyriacus . We used a STA-R Max coagulation analyser and TEG5000 thromboelastographers to test 47 Australian elapid venoms from 19 genera against human plasma in vitro. In addition to activity being confirmed in the two clades above, FXa-driven potent procoagulant activity was found in four additional genera ( Cryptophis, Demansia, Hemiaspis, and Suta ). Ontogenetic changes in procoagulant function was also identified as a feature of Suta punctata venom. Phylogenetic analysis of FX sequences confirmed that snake venom FXa toxins evolved only once, that the potency of these toxins against human plasma has increased in a stepwise fashion, and that multiple convergent amplifications of procoagulant activity within Australian elapid snakes have occurred. Cofactor dependence tests revealed all procoagulant venoms in our study, except those of the tiger snake clade, to be highly calcium-dependent, whereas phospholipid dependence was less of a feature but still displayed significant variation between venoms. Antivenom testing using CSL Tiger Snake Antivenom showed broad but differential cross-reactivity against procoagulant venoms, with P. porphyriacus and S. punctata extremely well neutralised but with Cryptophis, Demansia, and Hemiaspis less well-neutralised. The relative variation was not in accordance to genetic relatedness of the species used in antivenom production ( Notechis scutatus ), which underscores a fundamental principle that the rapid evolution characteristic of venoms results in organismal phylogeny being a poor predictor of antivenom efficacy. Our results have direct and immediate implications for the design of clinical management plans in the event of snakebite by such lesser known Australian elapid snake species that have been revealed in this study to be as potent as the better studied, and proven lethal, species.